Adverse events and retention of donors of double red cell units by apheresis - Keshelashvili, Ketevan; O'meara, Alix; Stern, Martin; Jirout, Zuzana; Pehlic, Vildana; Holbro, Andreas; Buser, Andreas; Sigle, Jörg; Infanti, Laura (Blood transfusion = Trasfusione del sangue, 2016)
Safety of double-erythrocyte (2RBC) collection and reasons for ceasing 2RBC donation were retrospectively analysed in the blood donor population of Basel, Switzerland. Donors with at least 1 2RBC apheresis were included in the study. Minimal requirements were Hb ≥140 g/L and body weight ≥70 kg; serum ferritin (SF) values were measured routinely, but were not part of the selection criteria. 2RBC collections were performed with ALYX devices at 6-month intervals. Adverse events (AEs) were systematically recorded and classified according to the ISBT EHN 2008 criteria. Data of procedures were retrieved from the ALYX software. Demographics, apheresis data and AEs were analysed with descriptive statistics. Data of 4,377 2RBC aphereses performed in 793 donors (779 males) between 1(st) January 2003 and 31(st) May 2015 were evaluated. Mean donor age at first 2RBC donation was 44 years (standard deviation [SD] 21), median number of donations was 4 (interquartile range [IQR] 8); 32% of the donors underwent a single procedure. There were 161 AEs, mostly local haematomas (55%) and vasovagal reactions (20%); fatigue was reported in 6% of the cases and was more frequent than citrate toxicity. Two severe AEs were observed. The most frequent reasons for abandoning 2RBC donation were low SF levels and donor choice (both 11%), but most donors simply did not reply to invitations (16%). Overall, procedure-related causes (AEs, low SF levels, no time for apheresis, inadequate venous access) were observed in 14% of the cases. At the end of the observation period, 40% of the donors were still active blood donors, but only 20% were donating 2RBC. 2RBC donation is overall safe. Donor retention was low over a period of 11 years. An important reason for abandoning 2RBC was the detection of low SF levels. The impact of fatigue on donor retention and the course of iron stores after repeated 6-monthly 2RBC apheresis require further investigation.